Wear Analysis of Tungsten Carbide Coated with Diamond-Like Carbon as Friction Stir Welding Tool - ABD MOKTI, NOORAKBAR (IRC, 2016)
Friction stir welding (FSW) is the new alternative to weld the aluminium matrix composite (AMC) to replace conventional welding as it produces joint with porosity. But the current tool, steel tool undergoes severe wear because of the contact between the tool and reinforcement in AMC. There are many methods of improving the wear rate of the tool and one of the methods is by using harder material.Therefore, this thesis resembles the wear analysis of the tungsten carbide coated with diamond like carbon (DLC) coating as friction stir welding (FSW) tool on aluminium matrix composite (AMC). The wear rate of the tool was calculated by the change of the mass and area after each welded joint.